MEMAHAMI DAMPAK PARADOKSAL INOVASI ANGGARAN TERHADAP KINERJA MANAJERIAL DALAM KONTEKS NEGARA BERKEMBANG - Okto Irianto; Fenty Yoseph Manuhutu; Andi Mattulada; Muliati Muliati; Rudy Usman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
Despite widespread promotion of budgetary innovation in developing countries, empirical evidence reveals contradictory performance outcomes that remain inadequately explained. This study investigates budgetary innovation's paradoxical effects on managerial performance in developing country public sectors. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) with data from 230 structural officials across 27 Indonesian government agencies in Merauke Regency (100% response rate), we find that budgetary innovation produces significant negative direct effects on managerial performance (β = -0.156, p = 0.013) while simultaneously generating equally strong positive indirect effects through enhanced job satisfaction (β = +0.156, p < 0.001), resulting in complete offsetting with near-zero net impact. Grounded in the Job Characteristics Model and Affective Events Theory, findings demonstrate that innovations disrupt performance through operational challenges, learning demands, and resource constraints while enhancing performance through improved work meaningfulness, autonomy, skill variety, and feedback mechanisms. The paradox reconciles contradictory evidence in existing literature and suggests public sector leaders should anticipate temporary performance decrements while deliberately investing in participatory implementation, comprehensive training, and satisfaction enhancement strategies to achieve net positive outcomes in resource-constrained developing country contexts.